Resistance Band Training To Increase The Arm Muscles Strength In Swimming Athletes - Rusmi Rusmi; Andi Heri Riswanto; Rachmat Hidayat; Ahmad Ahmad (JUARA : Jurnal Olahraga, 2023)
This study aims to determine the effect of resistance band training on arm muscle strength in freestyle swimming athletes at Palopo city swimmers. The method used in this study is an experimental one-group pretest-posttest design with a quantitative approach from the research that has been carried out on the effect of resistance band training on the arm muscle strength of swimming athletes in Palopo. And The result of this research shows an increase in arm muscle power by applying resistance band training on Palopo swimming athletes. Thus, there is a significant relation between Resistance band training towards the arm muscle power of Palopo freestyle swimming athletes.